2009
DOI: 10.1007/s00264-009-0768-3
|View full text |Cite
|
Sign up to set email alerts
|

Four-strand hamstring tendon autograft versus LARS artificial ligament for anterior cruciate ligament reconstruction

Abstract: This retrospective study compared the results after anterior cruciate ligament (ACL) reconstruction using a four-strand hamstring tendon graft (4SHG) versus Ligament Advanced Reinforcement System (LARS) artificial ligament in 60 patients between January 2003 and July 2004 with a minimum four-year follow-up. The KT-1000 examination, the International Knee Documentation Committee (IKDC) scoring systems and Lysholm knee scoring scale were used to evaluate the clinical results. The mean side-to-side difference was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 25 publications
1
64
1
1
Order By: Relevance
“…In five of the 16 papers available as full-text, the LARS™ ligament was compared to autografts (two BPBT and three 4SHG) [17,19,20,31,33]. The results showed that there were no significant differences between the two groups and that the patients treated with LARS™ had a faster recovery and return to sport activities without complications, such as synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…In five of the 16 papers available as full-text, the LARS™ ligament was compared to autografts (two BPBT and three 4SHG) [17,19,20,31,33]. The results showed that there were no significant differences between the two groups and that the patients treated with LARS™ had a faster recovery and return to sport activities without complications, such as synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 156 articles were excluded for one or more exclusion criteria: no full text available (n02), abstract or full text review revealing the article was not relevant (n0126), foreign language article for which no English translation was readily available (n030), evidence of data replication (n013) and studies relating to first-or secondgeneration devices not comparable to LARS (n037). Nine studies were included in the final review [5][6][7][8][9][10][11][12][13].…”
Section: Search Strategymentioning
confidence: 99%
“…The largest comparative study of LARS vs HS grafts, Liu et al [45] retrospectively compared 28 LARS and 32 HS grafts and found no significant differences between the two except in KT-1000 examination results showing the LARS to be more stable (1.2 mm vs 2.4 mm). However there were no differences in IKDC or revision rates.…”
Section: Synthetic Graftsmentioning
confidence: 99%